Depression and oral health-related quality of life: A longitudinal study - Nataliya Nerobkova; Nataliya Nerobkova; Eun-Cheol Park; Eun-Cheol Park; Sung-In Jang; Sung-In Jang (Frontiers Media S.A., 2023)
ObjectivesGeriatric oral health-related quality of life is a relatively new but rapidly growing concept as it is directly related to the general wellbeing and self-esteem of older adults. This study assessed the impact of worsening depression symptoms on oral health-related quality of life using representative nationwide data of Korean older adults.MethodsThis study comprised a longitudinal sample of older adults aged ≥60 from the Korean Longitudinal Study of Aging (2016-2020). After applying the exclusion criteria, 3,286 participants were included in the study. Depression status was determined through the biennial assessment of the short-form Center for Epidemiologic Studies Depression Scale (CESD-10); oral health was measured using the Geriatric Oral Health Assessment Index (GOHAI). We employed the lagged general estimating equations to assess the temporal effect of the CESD-10 score change on the GOHAI score.ResultsA decrease in CESD-10 score over a 2-year period was significantly associated with a decrease in GOHAI score in men and women: β = −1.810 and β = −1.278, respectively (p-values < 0.0001). Furthermore, compared to the same or improved CESD-10 score, worsening of the score on 1-2 points detected the β = −1.793 in men and β = −1.356 in women, and worsening on ≥3 points: β = −3.614 in men and β = −2.533 in women.ConclusionsThis study found that depression exacerbation is negatively associated with oral health-related quality of life in later life. Further, a more significant worsening of depression symptoms was correlated with lower scores for oral health-related quality of life in our study population.